Produção e caracterização de quitinase fúngica: aplicações na biodegradação de resíduos de quitina da Indústria Pesqueira - Rocha, Paula Maria Carneiro (2024)
Chitin is one of the most abundant homopolysaccharides in nature, composed of Nacetyl-glucosamine units. It is present in many organisms, mainly in crustaceans, arthropods and in the cell walls of fungi and yeasts. It is found in nature in three isoforms, α, β and γ and can be hydrolyzed by chitinases (E.C 3.2.1.14), extracellular enzymes produced by bacteria, fungi, viruses and plants that break the β-1,4 bonds of the chitin structure. These enzymes are divided into two large groups: endochitinases and exochitinases and have applications in various biotechnological sectors, such as pharmaceutical, food, biomedical and in the environmental control of agricultural pests as insecticidal and bactericidal agents. The enzymatic production of chitinases by microorganisms offers economical and efficient alternatives to industrial processes, making it possible to disuse conventional chemical agents. Following this approach, this work investigated the production of extracellular chitinase by the fungus Cunninghamella echinulata PA3S12MM, which until now had not been described in the literature. The fungus was grown in liquid Czapeck medium supplemented with different carbon sources at 28 °C under stationary culture conditions for up to 14 days. The highest enzyme production was obtained on the tenth day of cultivation with tilapia scales as a carbon source, presenting 5.20 U mL-1 in the initial cultivation conditions. The optimum pH and temperature for enzymatic activity of the chitinase enzyme were 4.5 and 55 °C respectively. When ideal enzyme conditions were associated, there was a 220% increase in enzyme activity, reaching 22.76 U mL-1. The molecular weight of the enzyme was estimated at 70kDa. Analysis of the images obtained by scanning electron microscopy (SEM) indicated that the degradation of chitin residues from shrimp shells and tilapia scales in natura was effective within 24 hours of enzymatic treatment, with no need to further purification of the enzyme to change the chitin structure. Also, results obtained from the analysis of the hydrolysis products of fresh shrimp shells by thin layer chromatography (TLC) indicated that the chitinase from C. echinulata PA3S12MM behaves like an endochitinase, with the release of chitooligosaccharides such as chitotriose (GlcNAc)3. Therefore, the filamentous fungus C. echinulata PA3S12MM was efficient in the production of chitinase and in the degradation of fishing waste like shrimp shells and tilapia scales, presenting satisfactory biochemical characteristics for applications in the sectors of sustainable industrial waste management without the need for treatments like acidic or basic chemicals that are harmful to the environment.